The precise ambit of the sealing requirement for deeds - TAN, Robbie Shih Rong (Institutional Knowledge at Singapore Management University, 2022)
Parties (“creditors”) who loan money to others (“debtors”) are often concerned that the debtors will be unable or unwilling to repay them. Such creditors may then enter into deeds of guarantee with third parties (“guarantors”) to secure the repayment of their loans if their debtors default on payment of the same. Unlike a contract, a deed does not require consideration to be legally enforceable. However, for a deed to be legally enforceable, several other formalities must be fulfilled. In particular, the deed must be “signed, sealed, and delivered”.